2009
DOI: 10.1194/jlr.m800184-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of structural heterogeneity in native lipooligosaccharides of Neisseria and cytokine induction

Abstract: Fine differences in the phosphorylation and acylation of lipooligosaccharide (LOS) from Neisseria species are thought to profoundly influence the virulence of the organisms and the innate immune responses of the host, such as signaling through toll-like receptor 4 (TLR4) and triggering receptor expressed on myeloid cells (TREM). MALDI time-of-flight (TOF) mass spectrometry was used to characterize heterogeneity in the native LOS from Neisseria gonorrheae and N. meningitidis. A sample preparation methodology pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
72
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 44 publications
15
72
1
1
Order By: Relevance
“…The addition of PEA to N. flavescens lipid A resulted in an increased cytokine response from THP-1 cells (SI Appendix, Fig. S4) (25)(26)(27). These results confirmed that the recombinant DDM solubilized enzyme was enzymatically active and able to induce a cytokine response.…”
Section: Resultssupporting
confidence: 72%
“…The addition of PEA to N. flavescens lipid A resulted in an increased cytokine response from THP-1 cells (SI Appendix, Fig. S4) (25)(26)(27). These results confirmed that the recombinant DDM solubilized enzyme was enzymatically active and able to induce a cytokine response.…”
Section: Resultssupporting
confidence: 72%
“…MS of intact LOS of the group C strain, 89I, did find multiple lipid phosphoforms (42,43), but this might have been an exception. What effects, if any, the different lipids might have on glycose antigen formation (48,49) were not explored.…”
Section: Discussionmentioning
confidence: 99%
“…Mass Spectrometry-Intact 7946 and 8024 LOS and O-deacylated LOS of 7946 and its ⌬lst and ⌬lgtB mutants were analyzed by negative ion matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), as described (40,42,43). MALDI-TOF MS was performed in the linear as well as the reflectron mode on a Voyager-DE STR instrument equipped with a 337-nm nitrogen laser and delayed extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOS was purified, and the relative abundances of the lipid A phosphoforms were determined. We have previously shown that there can be losses of phosphoryl substituents from lipid A when the OS moiety has been cleaved by acidic hydrolysis of LOS and when the LOS is de-O-acylated to remove O-linked acyl groups (10). Thus, we analyzed the LOS intact using previously described methods on a Synapt G2 HDMS system for high mass resolution negative-ion matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) (10,11).…”
mentioning
confidence: 99%